Anticipatory Traders and Trading Speed. (28th August 2018) - Fishe, Raymond P. H.; Haynes, Richard; Onur, Esen
Abstract : We examine whether speed is an important characteristic of traders who anticipate local price trends. These anticipatory participants correctly trade prior to the overall market and systematically act before other participants. They use manual and algorithmic order entry methods, but most are not fast enough to be high frequency traders (HFTs). Those anticipating price trends have impacts as if they are informed traders, while the case for anticipatory participants affecting the volume of other traders is rejected. A follow-up sample shows significant attrition in accounts and difficulty maintaining the anticipatory strategies. To identify anticipatory traders, we devise novel methods to isolate local price trends using order book data from the West Texas Intermediate (WTI) crude oil futures market.